PENGARUH KEGIATAN TILAWAH AL-QUR’AN TERHADAP MINAT MEMBACA AL-QUR’AN SANTRI - Muhtarom Muhtarom (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
This research aims to determine the effect of Al-Qur'an recitation activities on the interest in reading the Al-Quir'an of students at the As-Syafi'iyah Islamic boarding school, Durisawo Ponorogo. This type of research is quantitative with the observation location of the As-Syafi'iyah Islamic boarding school Durisawo Ponorogo, with data collection procedures through observation techniques, questionnaires, interviews and documentary studies. The data collected related to Al-Qur'an recitation activities and students' interest in reading Al-Qur'an were analyzed descriptively quantitatively, while data related to the effect of Al-Qur'an recitation activities on students' interest in reading Al-Qur'an were analyzed through product moment formula (correlation map). Based on the results of data analysis, it can be concluded that (1) The implementation of Al-Qur'an recitation activities for students at the As-Syafi'iyah Islamic boarding school Durisawo Ponorogo is in the good category, (2) Interest in reading the Al-Qur'an for students at the As-Syafi' Islamic boarding school iyah Durisawo Ponorogo in the medium category, and (3) there is a strong influence of Al-Qur'an recitation activities on the interest in reading the Al-Qur'an of As-Syafi'iyah Islamic boarding school students Durisawo Ponorogo.